A inclusão no ensino superior: atenção psicossocial aos discentes com necessidades educacionais da Universidade Estadual de Feira de Santana - Rodrigues, Ana Alice Brandão (2019)
The aims of this research consisted in identifying, describing and analyzing the representations of educational needs expressed in the demands of students of the State University of Feira de Santana (UEFS) from reports recorded by the team of Psychosocial and Educational Support Core (NAPP), relating to the objectives of the Institutional Policy of Inclusive Education of UEFS. With this, we analyze the inclusion of students with educational needs from the implementation of this policy in UEFS, from 2011 to 2016. It is a documentary study, with a qualitative approach that analyzed the records of the students attended in psychosocial attention by the NAPP team, based on the social inclusion model. The data were analyzed in order to understand the representations of the psychosocial demands of students with educational needs under Axel Honneth’s Theory of Recognition (2009). The research reveals that the inclusion of these students in Higher Education is permeated by the struggle for recognition each time they feel disrespected. It was also identified that the implementation of UEFS’ Institutional Policy for Inclusive Education does not effectively guarantee the rights of students with educational needs, although, on the other hand, it can be affirmed that the bonds of friendship between the students enabled the affective recognition. In addition, it was found the existence of solidarity relations between the students and some teachers, with respect and appreciation of the differences. Based on the results, it is possible to suggest that, through psychosocial attention, a network of strengthening of bonds be formed so that these students, based on the recognition patterns, fight for inclusion in Higher Education, aiming at the construction of values for an inclusive culture. This perspective demands a change of attitudes, as well as the recognition and appreciation of differences and diversity in search of the expansion of the movement for inclusion in Higher Education.